2012
DOI: 10.31989/ffhd.v2i5.93
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of Genistein-Cytoreg® combination in breast cancer cells

Abstract: Background: In spite the heavy investments in therapeutic research breast cancer still impacts the lives of women globally. The projected incidence of new cases of in situ breast cancer in the USA for 2011 is 57,650, with estimated 39,520 deaths. The phytoestrogen, genistein and the synthetic compound, Cytoreg® have been shown to inhibit growth and proliferation in many cancer cell lines. Purpose of the Study: In this study, we investigated the therapeutic efficacy of Cytoreg®-genistein combination on growth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One of the reported therapeutic effects of Cytoreg is the inhibition of the growth and proliferation of many cancer cell lines. 36 Our findings indicate that Cytoreg has an important effect on cellular metabolism by increasing mitochondrial activity, and suggest a mechanism for cancer cell apoptosis through the generation of reactive oxygen species, which may be considered a therapeutic mechanism of action that alters cellular metabolism from a hypoxic, oxygen-deficient state with an initial pO 2 of 84.6 ± 7.97 mmHg to a totally aerobic environment 147.3 ± 10.1 mmHg 60 minutes after administration. This mechanism of action not only influences the growth of neoplastic tissue but also affects the aforementioned illnesses, which are related to proper mitochondrial function.…”
Section: Discussionmentioning
confidence: 69%
“…One of the reported therapeutic effects of Cytoreg is the inhibition of the growth and proliferation of many cancer cell lines. 36 Our findings indicate that Cytoreg has an important effect on cellular metabolism by increasing mitochondrial activity, and suggest a mechanism for cancer cell apoptosis through the generation of reactive oxygen species, which may be considered a therapeutic mechanism of action that alters cellular metabolism from a hypoxic, oxygen-deficient state with an initial pO 2 of 84.6 ± 7.97 mmHg to a totally aerobic environment 147.3 ± 10.1 mmHg 60 minutes after administration. This mechanism of action not only influences the growth of neoplastic tissue but also affects the aforementioned illnesses, which are related to proper mitochondrial function.…”
Section: Discussionmentioning
confidence: 69%
“…Cytoreg is an experimental therapeutic technology platform consisting of an aqueous solution of hydrofluoric, hydrochloric, sulfuric, phosphoric, citric, and oxalic acids [ 1 ]. In vitro and in vivo studies have shown Cytoreg to have oncolytic activity [ [2] , [3] , [4] , [5] ]. In Wistar rats, oral administration of Cytoreg is well tolerated [ 6 ] and was recently shown to increase arterial blood oxygen pressure (pO 2 ) by iv administration [ 7 ].…”
Section: Introductionmentioning
confidence: 99%